Effectiveness of structured teaching programme on knowledge regarding ECG and its basic interpretation among second semester BSc Nursing students in selected nursing college at Pathanamthitta district - Aksa Maria Saji; Anaswara Pradeep; Ann Maria Kurian; Juliya Jose; Muhammed Hashim N.; Riya Baiju; Sruthi B.; Tesu James; Sony Aleyamma D. (International Journal of Biomedical Innovations and Engineering, 2023)
Cardiovascular diseases have now become the leading cause of mortality in India. Cardiovascular disease accounts for twenty five percent of all mortality. Electrocardiogram has an important role in the early detection and treatment of various cardiovascular diseases. Over the year significant advancements have been made in the field of ECG research, leading to the development of new techniques, technologies and algorithms for ECG analysis. ECG allows nurse to diagnose and monitor various cardiac conditions including arrhythmia, myocardial damage and provides quick management to the condition. If the nurse has to respond to this condition, it is essential to know about ECG and its basic interpretations. Efficacy in interpreting normal and pathological ECG is vital to determine any cardiac abnormalities and initiate the appropriate care required. Theoretical knowledge and practical skill on the recognition of pathological ECG trace improve the skill of ECG evaluation among nursing students. Accurate ECG interpretation by nurses leads to rapid recognition and treatment of cardiac emergencies and thereby reducing morbidity and mortality related to cardiovascular diseases.The current study aimed to assess the pre-test level of knowledge regarding ECG and its basic interpretations among second semester BSc Nursing students,assess the effectiveness of structured teaching programme on knowledge regarding ECG and its basic interpretations and to find the association between the existing level of knowledge regarding ECG and its basic interpretations with selected sociodemographic variables. The chosen research design for this study is a pre- experimental design featuring a single-group pre-test post-test structure.The study was conducted in Holy cross college of Nursing ,Adoor,Pathanamthitta. By using purposive sampling technique 30 second semester BSc Nursing students, who have met the inclusion criteria, were selected as samples. After identifying the knowledge regarding ECG and its basic interpretations by structured knowledge questionnaire Students were given structured teaching programme on ECG and its basic interpretations.The follow-up assessment was carried out utilizing the identical instrument. Majority of the study subjects were unaware of ECG and its basic interpretations. The administration of structured teaching programme helped to improve level of knowledge among second semester BSc Nursing students regarding ECG and its basic interpretations. The study results revealed that p value was significant for only gender among socio demographic variables.KEY WORDS: ECG ,structured teaching programme,questionnaire,knowledge,
Keywords: ECG; Knowledge; questionnaire; structured teaching programme